Nanowires: Fibroblasts Cultured on Nanowires Exhibit Low Motility, Impaired Cell Division, and DNA Damage (Small 23/2013). Issue 23 (9th December 2013) - Persson, Henrik; Købler, Carsten; Mølhave, Kristian; Samuelson, Lars; Tegenfeldt, Jonas O.; Oredsson, Stina; Prinz, Christelle N.
<x xml:space="preserve">Abstract</x> Mouse fibroblasts cultured on 7‐μm‐long vertical nanowires are reported on page 4006 by C. N. Prinz and co‐workers. Culturing cells on this kind of substrate interferes greatly with cell function, causing the cells to develop into widely different morphologies. The cells' division is impaired, in many cases leading to large multinuclear cells. Cell motility is also impeded, something the large cluster surrounded by unoccupied substrate bears witness to for this otherwise motile cell line. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>